Comparing quantitative and qualitative verbal and social autopsy tools: does a qualitative supplement improve understanding of the social determinants of under-five deaths in the slums of Kampala, Uganda? - Amy W Blasini; Peter Waiswa; Ann Wolski; Phillip Wanduru; Chelsea Finkbeiner; Ashura Bakari; Lucky Amutuhaire; Cheryl A Moyer (Journal of Global Health Reports)
# Background